Bimetallic Pt3Co nanowires as electrocatalyst: the effects of thermal treatment on electrocatalytic oxidation of Methanol. (10th April 2015) - Su, Y.K.; Liu, H.; Feng, M.; Yan, Z.L.; Cheng, Z.H.; Tang, J.N.; Yang, H.T.
Abstract: The influence of thermal treatment effect on the methanol oxidation catalytic activities of Pt3 Co alloy nanowires prepared by template-assisted pulsed electrodeposition has been investigated. The catalytic activities of Pt3 Co nanowires dose not linearly increase as the annealing temperature rises from 200 to 600 °C, in which the best catalytic performance appear at 200 °C. Meanwhile, the perpendicular coercivity has a weak increase at a mild thermal treatment from 200 to 400 °C and a dramatic increase after annealing at 600 °C. These results reveal that the thermal treatment has a strong influence on their catalytic and magnetic properties of electrodeposited Pt3 Co alloy nanowires and can be exploited as an effective and facile way to achieve excellent magnetic nanocatalyst.